The Role of Transportation Accessibility and Public Facilities on Tourism Experience in Tourist Destinations in Central Java - Adrial Adrial; Arief Sulistiyono; RD. Hera Merdeka Khazinatul Khaeriah (West Science Interdisciplinary Studies, 2026)
This study investigates the influence of transportation accessibility and public facilities on the tourist experience in tourist destinations in Central Java, Indonesia. A quantitative research approach was employed using survey data collected from 200 tourists. The research instrument was a structured questionnaire measured using a five-point Likert scale. Transportation accessibility and public facilities were examined as independent variables, while tourist experience served as the dependent variable. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25, applying descriptive analysis, validity and reliability tests, and multiple linear regression analysis. The results indicate that transportation accessibility has a positive and significant effect on tourist experience, demonstrating that ease of access, transportation availability, and connectivity contribute substantially to tourists’ overall perceptions. Public facilities also show a positive and significant effect, highlighting the importance of adequate amenities such as sanitation, parking, signage, and information services in enhancing comfort and satisfaction. Furthermore, both variables simultaneously explain a substantial proportion of the variance in tourist experience. These findings underline the importance of integrated transportation systems and well-maintained public facilities in improving tourist experience and strengthening destination competitiveness in Central Java.